Принципы построения информационной технологии самоорганизации базы даннях сервис-ориентированной информационной системы - Васильцова, Н. В.; Неумывакина, О. Е.; Панфёрова, И. Ю. (My University, 2013)
The basic principles of information technology that will solve the problem of self-organization of a database in a service-oriented information system. Highlights the main principles of the technology. Offers basic construction principles, which define the basic architectural solutions of the technology. Основні принципи інформаційних технологій, які дозволять вирішити проблему самоорганізації бази даних в сервіс-орієнтованій інформаційній системі. Виділено основні принципи технології. Пропонуються основні принципи побудови, які визначають основні архітектурні рішення технології.
Keywords: информационная система; самоорганизация